Pacing Spikes All Over. Issue 11 (22nd June 2017) - Shurrab, Mohammed; Pagacz, Teresa; Shauer, Ayelet; Lashevsky, Ilan; Newman, David; Crystal, Eugene
Ventricular safety pacing (VSP) is used to avoid cross talk by delivering ventricular stimulus shortly after an atrial-paced event if ventricular-sensed event occurs. Although VSP is a protective feature that exists for decades in different pacing devices, there are some reports of unfavorable outcomes of this algorithm. More so, health care providers sometimes face difficulties in interpreting and dealing with VSP strips. This case report discusses an important pacemaker algorithm and encourages further attention to possible pitfalls and hence avoids unnecessary interventions.